The Effect of Capital Structure on Firm's Profitability: A Case of Listed Malaysian Industrial Firms - Mohamad Khan, Raji Jamal (1994)
This paper attempts to examine the influence of capital structure, particularly in the presence of market imperfections on firm's profitability. The effect of corporate taxes, interest expense, debt level and equity size is analyzed using OLS estimates and correlation analysis. The research model justifies that capital structure changes in response to market imperfections which subsequently affect profitability. This findings empirically implies that: (a) higher debt level result in a lower profitability; (b) higher profitability associates positively with taxation expense but negatively with interest expense.